Chloramphenicol-induced gray baby syndrome: case report and review of current literature - Fang, Yu; Luo, Rong; Chen, Xiaolu (Frontiers in Pediatrics, 2026)
BackgroundGray baby syndrome is a severe adverse reaction to chloramphenicol, with a mortality rate up to 40%.MethodsWe report a case in which a 14-month-old Yi boy accidentally ingested 1.5 g of chloramphenicol (6 × 0.25 g tablets) that his grandmother had left on a coffee table, mistaking them for food, which led to and was diagnosed by circulatory failure (blood pressure: 87/50 mmHg), metabolic acidosis (pH: 7.131), hypothermia (36.3°C), serum drug level (92 μg/mL), and multiorgan damage; critical interventions included mechanical ventilation, vasopressors, and delayed continuous renal replacement therapy (initiated 18 h after ingestion). Besides his case, 19 other published cases were analyzed.ResultsThe child recovered fully after 3 weeks with no sequelae noted at 20-month follow-up. Literature analysis revealed 64.7% survival (11/17) and 35.3% mortality (6/17), with fatal cases consistently showing serum chloramphenicol levels exceeding 50 μg/mL.ConclusionsDespite typical mortality risks, delayed CRRT proved pivotal in reversing toxicity in our patient. Gray baby syndrome continues to occur in underserved regions, necessitating strict drug storage, serum concentration monitoring in high-risk infants, and early CRRT implementation for survival.